The Role of Family in the Development of Child’s Religious Beliefs - Mammadov, Azad (Scholarya Demo Journal of Ruby, 2019)
Childhood is a period of rapid development. Unlike other stages, children grow and develop more rapidly. Early directions and assistance during this period can have a lasting impact on individuals’ cognitive abilities, personality and social behavior. This is the most important stage where the development of a child should be controlled in a true and appropriate way. From this point of view, it is important to recognize and value children properly. It is generally accepted that all areas of development affect the individual’s future life. Emotions, thoughts, and behaviors are formed in childhood. Since the day they have been born, the personality of individuals is formed first by the influence of their family and further school as well as the social environment. During this time individuals are trying to make sense of their life by observing the behavior in their environment. Being a major period for an individual’s personality development, childhood plays an important role in the formation of one’s religious identity. The child is a potential believer who has feelings and believes naturally. The religious experience of adulthood is based on its childhood foundations. During this time, mothers and fathers who have the significant influence on children are their role models. Proper parenting of the child's religious beliefs and emotions, which are open to development, is one of the important factors that influences his religious cognition and attitude to religion in his future life. The main purpose of this study is to reveal the role of parents’ religious instruction and behavior in the development of children’s religious beliefs.